ANALISIS PERBANDINGAN KASUS RAHASIA DAGANG (STUDI KASUS:PUTUSAN NOMOR 332 K/PID.SUS/2013 (INDONESIA) DENGAN PUTUSAN CIV. NO. 3:13-CV-00098-AA (AMERIKA SERIKAT). - Jessica Kirana Budi (Faculty of Law, Universitas Lampung, 2021)
The importance of trade secrets being well understood by the public or business firms has become the subject of increasing domestic and international policymaking. So it is essential to analyze a trade secret case, which in this case is the case of CV Bintang Harapan with CV Tiga Putra Berlian VS Reser’s Fine Foods, INC with Bob Evans Farms, INC. This research compares cases of trade secrets between CV Bintang Harapan with CV Tiga Putra Berlian VS Reser’s Fine Foods, INC with Bob Evans Farms, INC? Then, from these comparisons, what appropriate solutions can be given from this research? This study uses a normative legal writing research method with a case approach. The results showed that in the case comparison analysis between CV Bintang Harapan with CV. Tiga Putra Berlian VS Reser's Fine Foods, INC with Bob Evans Farms, INC. Is divided into 6 (six) analysis as follows: the first is related to evidence regarding trade secrets, then the second is related to the existence of work agreement arrangements regarding confidentiality agreements with researchers with employees, the third relates to decisions or acquittals of pure or impure free on a CV Bintang Harapan with CV Tiga Putra Berlian, whereas in the case of trade secrets Reser's Fine Foods, INC with Bob Evans Farms, INC does not recognize impure decisions or acquittals, but decisions with prejudice decisions without prejudice or Voluntary Dismissal Without Prejudice. The fourth relates to the arrangement of attorney fees. The fifth is related to compensation, and the last one is related to the Economic Espionage Act. The 6th is related to the law enforcement process in court. Based on this comparison, the authors suggest that protecting trade secrets can be done through work agreements, and in solving trade secret cases, it can be done by proving the misuse of trade secrets.